Education mining in the relationship between general knowledge and deep knowledge for lifelong learning - Pratya Nuankaew (2018)
© 2017 IEEE. Transforming the Thai society into a knowledge-based one requires enabling all Thais to have equal access to education and the development of human resources through continuous lifelong learning, as outlined by the objective of Thailand's National Education Standards. Thus, this paper aimed to study and identify the relationship between general knowledge and depth knowledge for lifelong learning in higher education. The data collection was conducted from 411 randomly selected students from Rajabhat Mahasarakham University, Thailand. As the results showed, it is clear that there is an opportunity for general education to affect a particular course by about half the total. However, analysis of the data may have employed only some of the data collected.